Krytyczna refleksja o stanie współczesnej edukacji wczesnoszkolnej – ujęcie porównawcze - Wiśniewska-Kin, Monika (Wydawnictwo Naukowe UAM, 2016)
In an attempt taken to reconstruct the current issues in the field of early childhood education, what becomes particularly important are the questions related to the way of organizing education in Poland and around the globe, i.e. in diverse cultural environments. The current problems diagnosed can contribute to redefining the goals of the school. Without a recognition of the difficulties, it is impossible to determine the direction of research or an action plan towards an actual, substantial reform of education. In an effort to rebuild schools, it is therefore necessary to create a debate about development trends of education in the twenty-first century in Poland and in the world. The comparative perspective adopted can facilitate outlining a broad and multi-dimensional context decisive for the value of the educational discourse.
Critical Reflection on the State of Contemporary Early Childhood Education – a Comparative Approach
Keywords: determinants of the education system in Poland; early education; current problems in early childhood education